Biomonitoring of 89 POPs in blood serum samples of Czech city policemen. (15th December 2021) - Polachova, Andrea; Gramblicka, Tomas; Bechynska, Kamila; Parizek, Ondrej; Parizkova, Denisa; Dvorakova, Darina; Honkova, Katerina; Rossnerova, Andrea; Rossner, Pavel; Sram, Radim J.; Topinka, Jan; Pulkrabova, Jana
Abstract: In this biomonitoring study, we evaluated the concentrations of 8 polychlorinated biphenyls (PCBs), 11 organochlorinated pesticides (OCPs), 33 brominated flame retardants (BFRs), 7 novel brominated and chlorinated flame retardants (novel FRs) and 30 per- and polyfluoroalkylated substances (PFAS) in human serum samples (n = 274). A total of 89 persistent organic pollutants (POPs) were measured in blood serum samples of city policemen living in three large cities and their adjacent areas (Ostrava, Prague, and Ceske Budejovice) in the Czech Republic. All samples were collected during the year 2019 in two sampling periods (spring and autumn). The identification/quantification of PCBs, OCPs, BFRs, novel FRs and PFAS was performed by means of gas chromatography coupled to (tandem) mass spectrometry (GC–MS/(MS)) and ultra-high performance liquid chromatography coupled to triple quadrupole tandem mass spectrometry (UHPLC–MS/MS). The most frequently detected pollutants were perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA), perfluorooctanesulfonate (PFOS), perfluorohexanesulfonate (PFHxS), 2, 2′, 3, 4, 4′, 5′-hexachlorobiphenyl (CB 138), 2, 2′, 4, 4′, 5, 5′-hexachlorobiphenyl (CB 153), 2, 2′, 3, 3′, 4, 4′, 5-heptachlorobiphenyl (CB 170), 2, 2′, 3, 4, 4′, 5, 5′-heptachlorobiphenyl (CB 180), hexachlorobenzene (HCB), and p, p' -dichlorodiphenyldichloroethylene ( p, p′ -DDE) quantified in 100% of serum samples. In the serum samples, the concentrations of determined POPs were in the range of 0.108–900 ng g −1 lipid weight (lw) for PCBs, 0.106–1016 ng g −1 lw for OCPs, <0.1–618 ng g −1 lw for FRs and <0.01–18.3 ng mL −1 for PFAS, respectively. Locality, sampling season, and age were significantly associated with several POP concentrations. One of the important conclusions was that within the spring sampling period, statistically significant higher concentrations of CB 170 and CB 180 were observed in the samples from Ostrava (industrial area) compared to Prague and Ceske Budejovice. Older policemen had higher concentrations of five PCBs and two OCPs in blood serum. Highlights: Serum was used for assessment of direct human body burden to possible harmful POPs. 18 PFASs, 15 BFRs, 10 OCPs, 8 PCBs and 3 novel FRs were quantified in human serum. Within the dominant PFASs in serum, 11 new pollutants were included. A declining trend for PCB and OCP concentrations in serum was monitored. Selected PCB and OCP levels were found to increase with increasing policemen's age.